Effects of dissolved mercury on embryogenesis, survival and growth of Mytilus galloprovincialis mussel larvae - Beiras, R; His, Edouard (Marine Ecology Progress Series, 1995)
The effects of Hg concentrations ranging from 0 (control) to 1024 mu g l(-1) upon embryogenesis, survival and growth of Mytilus galloprovincialis mussel larvae were investigated. Embryogenesis was abnormal in 50% of the individuals at 10 mu g l(-1). The 48 h LC(50) for D-shaped, early umbonate, late umbonate and eyed larvae were 51, 164, 322 and 383 pg l(-1) respectively. The LC(50) was an allometric function of ash-free dry weight with exponent b = 0.60. Larval growth was significantly reduced after 6 d exposure to 4 mu g Hg l(-1) and after 10 d exposure to 2 mu g l(-1). No significant differences in lethal or sublethal sensitivity to Hg were found between M. galloprovincialis and previously studied Crassostrea gigas embryos and larvae. The implications of these findings for monitoring pollution by utilising different bivalve species are discussed.